Pengembangan Game Edukasi Android Mat Croco Berorientasi pada Penalaran Matematika - Hadi Sutrisno (Jurnal Didaktika Pendidikan Dasar, 2020)
In 2017, 36% of 43.7 million gamers in Indonesia were students. This development research aims to produce an android educational game Mat Croco has good quality (valid, practical, and effective). The type of this research is a research development (ADDIE model). The results of the Mat Croco validity test by two experts were stated to have good validity. It shown a media validity score 36.5 and a validity score about math reasoning is also 36.5. The results of the practicality analysis by two mathematics teachers and two students showed that the Mat Croco game had excellent practicality. The average score of practicality by 37 teachers and practicality scores of students 36. The results of the analysis effectiveness test game Mat Croco effectively oriented students' mathematical reasoning. Descriptive analysis has increased the average value of mathematical reasoning (pretest = 28.4 and posttest = 84.4) and the percentage of completeness (pretest = 0% and posttest = 75.9%). Paired Samples Test concluded that the Mat Croco game was effectively oriented towards mathematical reasoning (| t | (25,200)> t table (t 0.025; 28 = 2.368) and sig. (0,000) <0.0025). The results of the analysis show that the Mat Croco has good quality (valid, practical, and effective) and is worth applying in the mathematics learning of sequence and series mathematics.